Sterling, best dog ever - Cassie, Aidan (New York : Farrar Straus Giroux, 2018)
"Sterling the dog has always wanted a home. But no home has ever wanted him. So when Sterling sees a sign on the side of the Butlery Cutlery Company advertising free "shipping to homes around the world," he is determined to become the most terrific fork ever! For what home doesn't need flatware? Sterling is delivered on time and undamaged to the Gilbert family's front door. He is not, however, what they ordered ... But he may be exactly what they need. Here is a humorous, heart-tugging picture book about finding a family who wants you just as you are." -- Dust jacket.
Title has the word Fork crossed out and corrected to Dog.
Keywords: Dogs -- Juvenile fiction; Pets -- Juvenile fiction; Dachshunds -- Juvenile fiction; Pets -- Juvenile fiction; Dogs -- Juvenile fiction; Dachshunds -- Juvenile fiction; Dachshunds; Dogs; Pets; Picture books; Fiction; Juvenile works; Picture books; Picture books